Frequency Fluctuations of the Doppler Signal - Baras, S. T.; Voitsekhovska, O. V.; Shcherbatiuk, H. M. (Visnyk of Vinnytsia Politechnical Institute, 2019)
An estimate of the fluctuations in the frequency of filling the Doppler signal is an important task in the context of determining the components of the velocity vector of a carrier by a hydroacoustic log. The mathematical model of the Doppler echo signal is analyzed from the point of view of the mechanism of its formation. The dominant influence on its carrier frequency of the partial signal corresponding to the axis of the antenna’s radiation pattern is substantiated. It is shown that in addition to the axial partial echo signal with high level, there are side partial echoes with different from "axial" frequencies, which, together with the axial partial echo signal, form the final Doppler echo signal arriving at the entrance to the receiver of the Doppler lag. The results of experimental studies of Doppler signals are presented in the paper. They testify to the low level of fluctuations of Doppler frequency shifts, which creates prerequisites for a high potential accuracy of determining the components of the velocity vector of carrier. It is shown that the fluctuations of the carrier frequency of the Doppler echo signal, which directly determines the carrier velocity, are negligible. The results of the processing of the frequency arrays obtained during the operation of the lag with the bottom signals in the form of the mean square values of the fluctuations of the frequency of the Doppler signal are given. They show that the carrier frequency of the Doppler signal is quite stable not only within the echo, but also over the entire range of measurements. Graphical dependences of Doppler shifts on different rays of a Janus configuration are also presented. They allow us to estimate the results of measurements of frequency and its fluctuations in the Doppler signal at a qualitative level. The rather low errors of the measurement of Doppler frequency shifts, which were obtained at the same time, characterize the high metrological characteristics of the Doppler logs.